How Does Negative Emotion Cause False Memories? - Brainerd, C. J.; Stein, L. M.; Silveira, R. A.; Rohenkohl, G.; Reyna, V. F. (Psychological science, 2008)
Remembering negative events can stimulate high levels of false memory, relative to remembering neutral events. In experiments in which the emotional valence of encoded materials was manipulated with their arousal levels controlled, valence produced a continuum of memory falsification. Falsification was highest for negative materials, intermediate for neutral materials, and lowest for positive materials. Conjoint-recognition analysis produced a simple process-level explanation: As one progresses from positive to neutral to negative valence, false memory increases because (a) the perceived meaning resemblance between false and true items increases and (b) subjects are less able to use verbatim memories of true items to suppress errors.